2019
DOI: 10.29327/ouricuri.9.2-1
|View full text |Cite
|
Sign up to set email alerts
|

BIOMETRY AND NON-DESTRUCTIVE ALLOMETRIC MODEL FOR ESTIMATING BABASSU (Attalea speciosa) FRUIT VOLUME AND DENSITIES

Abstract: Biometric data of fruits, such as volume and density, can be applied for different ecological and economic purposes. Non-destructive allometric models based on morphometric dimensions can be more accurate and practical in field conditions than destructive methods used in traditional growth curves. Babassu is a Brazilian native palm tree with wide distribution whose fruits are of high importance for socioeconomic and cultural purposes, in addition to having high potential for biodiesel production. The objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
(24 reference statements)
2
4
0
Order By: Relevance
“…destructive volume estimation models developed from easily measurable parameters for different type of fruits such as pepper [15,17], Babassu (Attalea speciosa) fruit [47], Karanda (Carissa carandas) fruit [31], and Apple fruit [48]. Our findings confirmed that non-destructive allometric models based on easily measurable morphometric dimensions can be more accurate…”
Section: Plos Onesupporting
confidence: 74%
“…destructive volume estimation models developed from easily measurable parameters for different type of fruits such as pepper [15,17], Babassu (Attalea speciosa) fruit [47], Karanda (Carissa carandas) fruit [31], and Apple fruit [48]. Our findings confirmed that non-destructive allometric models based on easily measurable morphometric dimensions can be more accurate…”
Section: Plos Onesupporting
confidence: 74%
“…Our allometric models could provide accurate estimate of avocado fruit volume and may reduce required time and financial resources while using common method of volume measurements like water displacement, gas displacement and expensive instruments, e.g., image processing software or machine vision techniques. In line with this, review literature showed that there are different non-destructive volume estimation models developed from easily measurable parameters for different type of fruits such as pepper [ 15 , 17 ], Babassu ( Attalea speciosa) fruit [ 47 ], Karanda ( Carissa carandas ) fruit [ 31 ], and Apple fruit [ 48 ]. Our findings confirmed that non-destructive allometric models based on easily measurable morphometric dimensions can be more accurate and practical in field conditions than destructive methods used in traditional growth curves [ 18 ].…”
Section: Resultsmentioning
confidence: 95%
“…[5] In fruits, morphometric measurements, such as weight, size, density, surface area, and volume, are correlated and essential. [6,7] In grading and sorting of vegetables and fruits, these measurements are often used as crucial descriptors. [8] The fruit size and weight directly influence storage and transport costs, eventually influencing sales and marketing prices.…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] Fruit volume and density relate to fruit consistency, carbon consumption, and water content used to forecast harvesting periods. [7,11] The average density, critical in identifying hidden defects such as frost and internal damage, can be determined when the weight is combined with the volume. [9] CONTACT Chen Kunjie kunjiechen@njau.edu.cn College of Engineering, Nanjing Agricultural University, Jiangsu, 210031, P. R. China…”
Section: Introductionmentioning
confidence: 99%